Evaluation of the effectiveness of educational escape rooms within health professions education: A systematic review protocol. (2023) - Bray, Lucy; Antoniou, Panagiotis; Nikolaidou, Maria; Fides-Valero, Álvaro; Roberts, Trudie; Ahonen, Outi; Häyrinen, Sini; Campos-Díaz, Eva; Bamidis, Panagiotis D.
Highlights: Detailed protocol of a systematic review exploring the evaluation of escape rooms. Defines the concept of an escape room. Outlines the current uses of escape rooms within health professions education. Describes the steps involved in a systematic review. Abstract: Escape rooms are being increasingly employed as an educational approach within health professions education. Given the rapid increase in their application, investigators have adopted diverse evaluation methods, many of which utilise ad-hoc instruments. To inform future evaluation methods and the adoption of validated evaluation instruments, a systematic review is planned. This protocol outlines the steps of this review, which will collate and synthesise the evidence related to the evaluation and efficacy of educational escape rooms within health professions education. A search, applying terms for escape rooms, healthcare professionals and evaluation, will be conducted using multiple databases. Studies will be screened against eligibility criteria and all eligible studies will be quality assessed using a validated tool. Data will be narratively synthesised.